Dynamics of Dental plaque Hygienic index modified by Turesky, Alpha-defensin and Rheological Status estimation in Patients Undergoing Orthodontic Treatment - N.A., Tamasidze; M.I., Nikolaishvili; N.G., Mosemghvdlishvili; S.R., Chikobava; M.A., Gogiberidze; A.G., Tamasidze (European Scientific Journal, ESJ, 2016)
Thus, the index of dental plaque was reliably low in patients undergoing the treatment by aligners as compared with the patients with fixed bracket-systems. Non-removable orthodontic equipment affects marginal periodontal tissues and mouth hygienic condition more than removable one. In spite of observed considerable data spread, when comparing the initial level of antimicrobial peptide measured before the placing the bracket systems, statistically significant differences were obtained. In mixed saliva in patients of basic group the content level of alpha-defensin was higher than in the control group. 3 months after carrying bracket systems value index significantly changed: in the group with inflammatory processes the content of alpha defensin decreases in periodontal tissues whilst in comparison group it increases. The changes in basic group after three months was significant. Thus data evaluation suggests that orthopedic problems are accompanied by blood rheological changes that lead to the increase in plasma viscosity red blood cells aggregability and decrease in red blood cells deformation. That is, (blood rheology) and coagulation changes are notable while dysfunction of vascular endothelium is present. These patients might be considered as riskgroups for cardiovascular problems.